2018
DOI: 10.1111/cea.13254
|View full text |Cite
|
Sign up to set email alerts
|

Birch pollen‐specific subcutaneous immunotherapy reduces ILC2 frequency but does not suppress IL‐33 in mice

Abstract: BP SCIT is able to suppress the adaptive and part of the innate immune response, but this is not sufficient to inhibit collagen deposition and the IL-33 expression in the airways in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…GM-CSF is known as a cytokine that induces differentiation of pluripotent hematopoietic stem cells into granulocyte-monocyte cells [23,24]. In relation to pollen allergy and GM-SCF, this cytokine has been reported to increase with IL-33 and IL-25 in animal models, and following the activation of neutrophils and antigen-specific T cells [25]. Additionally, one report has shown that IL-33 is activated by GM-CSF and IL-8 in the nasal mucosal epithelium of allergic rhinitis [26].…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF is known as a cytokine that induces differentiation of pluripotent hematopoietic stem cells into granulocyte-monocyte cells [23,24]. In relation to pollen allergy and GM-SCF, this cytokine has been reported to increase with IL-33 and IL-25 in animal models, and following the activation of neutrophils and antigen-specific T cells [25]. Additionally, one report has shown that IL-33 is activated by GM-CSF and IL-8 in the nasal mucosal epithelium of allergic rhinitis [26].…”
Section: Discussionmentioning
confidence: 99%
“…A murine airway inflammation model demonstrated a reduced proportion of IL5 + ILC2s in the circulation without affecting innate ILC-activating cytokines IL-33 and IL-25 after a 2month birch pollen-SCIT [107]. In contrast, a 4-month GP-SCIT in humans failed to induce alterations of ILC2 frequencies in the periphery [80].…”
Section: Effect Of Ait On Innate Immune Responsesmentioning
confidence: 97%
“… 21 , 22 Allergens such as ovalbumin and dust mites were used to sensitize and stimulate BALB/c mice to establish respiratory allergic inflammation mainly caused by Th2 mediated eosinophilic infiltration. 23 , 24 , 25 , 26 BALB/c mice immune responses tend to be Th2 response and are widely used for AR mice model. 27 However, C57BL/6 mice can be used as ILC2s mediated allergic inflammation, which reduce the influence of Th2 type adaptive immunity and better reflect the important role of innate immunity in respiratory allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%